Long term remission of Sjögren's syndrome associated aggressive B cell non-Hodgkin's lymphomas following combined B cell depletion therapy and CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone). Issue 8 (1st December 2005) - Voulgarelis, M; Giannouli, S; Tzioufas, A G; Moutsopoulos, H M
Abstract : Background: Primary Sjögren's syndrome (SS) is associated with an increased frequency of non-Hodgkin's lymphomas (NHLs), mainly of low histological grade. However, aggressive diffuse large B cell lymphomas (DLBCL) characterised by poor treatment outcome can also be encountered in SS. It has recently been shown that rituxan has significant therapeutic activity in this type of lymphoma. Objective: To evaluate the efficacy of CHOP chemotherapy (cyclophosphamide, doxorubicin, vincristine, prednisone) in combination with rituxan in SS patients with DLBCL, and to determine the outcome in such patients. Methods: In an open, single case trial, six SS patients with DLBCL were assigned to receive eight cycles of CHOP every three weeks plus rituxan given on day 1 of each cycle. In a retrospective study, conducted by the European Concerted Action for SS, nine cases were diagnosed as DLBCL, all of whom had been treated with CHOP alone. These patients were used as historical controls. Results: The difference in the overall survival between the two treatment groups was significant. The group treated with rituxan plus CHOP had a 100% two year overall survival rate, while the historical controls had only a 37% survival rate. Extraglandular manifestations serving as predictors for lymphoma development such as palpable purpura and peripheral neuropathy disappeared. The remission of these signs was accompanied by a decrease in both circulating monoclonal cryoglobulins and rheumatoid factor activity and an increase in C4 levels. Clinically relevant toxicity was not detected. Conclusions: The addition of rituxan to standard CHOP chemotherapy results in improved treatment outcome in SS patients with aggressive DLBCL, without increasing toxicity.